Jahresgaben 1988 : "Die Alljährliche". (München : Kunstverein München, 1988)
Achmann, Wolfgang ; Backhaus, Arno ; Bartscht, Dietrich ; Beers, Robin ; Böhmer, Michael ; Böllinger, Christoph ; Buhl, Bodo ; Colette ; Dillemuth, Stephan ; Dittmar, Peter ; Eckle, Michael ; Eickhoff, Jürgen ; Endriss, Lisa ; Fink, Ossi ; fischer, Rotraut ; Förg, Hubert ; Fritz, Reinhard ; Gerner, Wolfgang ; Gruchot, Heinz ; von Hagen, Beatrix ; etc.
Jahresgaben 1988 : "Die Alljährliche", Kunstverein München, 2. Dez. 1988 - 23. Dez. 1988
kunstcatalogus